2008
DOI: 10.1111/j.1600-051x.2008.01306.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of periodontal condition by probiotics with Lactobacillus salivarius WB21: a randomized, double‐blind, placebo‐controlled study

Abstract: Our results indicate that probiotics could be useful in the improvement/maintenance of oral health in subjects at a high risk of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
218
2
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(242 citation statements)
references
References 43 publications
8
218
2
14
Order By: Relevance
“…Ishikawa et al (2003), and Matsuoka et al (2006) demonstrated that the oral application of probiotic pills containing L. salivarius significantly reduced the concentration of the periopathogenic bacterium P. gingivalis in saliva and subgingival plaque in healthy volunteers. Shimauchi et al (2008) documented a reduced concentration of periodontopathogenic bacteria after the administration of probiotic Lactobacilli over a period of 8 weeks, which was associated with improved periodontal conditions. Although the characterization of the oral microflora was not the aim of this study, it may be speculated that the accumulation of a non-pathogenic bacterial biofilm on the tooth surfaces was very likely causative for the reduced inflammation in the test group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Ishikawa et al (2003), and Matsuoka et al (2006) demonstrated that the oral application of probiotic pills containing L. salivarius significantly reduced the concentration of the periopathogenic bacterium P. gingivalis in saliva and subgingival plaque in healthy volunteers. Shimauchi et al (2008) documented a reduced concentration of periodontopathogenic bacteria after the administration of probiotic Lactobacilli over a period of 8 weeks, which was associated with improved periodontal conditions. Although the characterization of the oral microflora was not the aim of this study, it may be speculated that the accumulation of a non-pathogenic bacterial biofilm on the tooth surfaces was very likely causative for the reduced inflammation in the test group.…”
Section: Discussionmentioning
confidence: 96%
“…Several clinical studies demonstrated that a regular consumption of probiotic lactobacilli and Bifidobacterium decreased the number of cariogenic streptococci in saliva and dental plaque, resulting in a significant lower risk of caries (Näse et al, 2001;Ahola et al, 2002;Ç aglar et al, 2006;Ç aglar et al, 2007;Cildir et al, 2009). Several studies also revealed that probiotic Lactobacillus strains were reducing gingival inflammation (Krasse et al, 2006;Twetman et al, 2009), improving periodontal health (Shimauchi et al, 2008) and decreasing the concentration of black-pigmented rods including Porphyromonas gingivalis in saliva and subgingival plaque (Ishikawa et al, 2003;Matsuoka et al, 2006). In contrast, Staab et al (2009) found no changes of clinical inflammatory parameters.…”
Section: Introductionmentioning
confidence: 99%
“…By using a probiotic treatment (L. reuteri) also clinical effects were found, like a significant reduction in the gingival index and plaque scores [56]. Smokers showed a significantly greater improvement in plaque scores in a clinical trial using freeze-dried probiotic tablets of L. salivarius [57]. Even heat-killed L. plantarum decreased the depth of periodontal pockets in a randomised, doubleblind, placebo-controlled clinical trial [58].…”
Section: Periodontal Diseasementioning
confidence: 99%
“…10 The most commonly used and studied probiotic are lactic acid bacteria, in particular Lactobacillus spp., and Bifidobacterium spp. 26 To determine the effects of probiotic on oral health promotion, we conducted a double blind, placebo-controlled randomized clinical trial in healthy subjects with gingivitis. The specific aim of this study was to investigate the effect of combined probiotic formulation on plaque, gingivitis and caries during and after discontinuation of administration.…”
Section: Journal Of Research and Practice Inmentioning
confidence: 99%